Challenges, differences and perspectives over an epidemic - José Augusto Simões de Miranda (Fórum Linguístico)
This study aims to investigate the discourse of an HIV campaign in Brazil, produced by Ministério da Saúde, which has four participants who discovered the HIV diagnosis at the beginning of the epidemic, as well as understand and discuss how they reacted to the diagnosis, whether they talk about differences in terms of advances over the epidemic, and whether the discourse analyzed in the campaign contributes to transforming the stigma that triggers prejudice and discrimination. The study was carried out following a qualitative research methodology and the data were discussed in the light of the theoretical-analytical approach of Critical Discourse Analysis and of the concept of biopolitics. The results show that, although the participants talk about different challenges they have faced since the beginning of the epidemic and its biomedical advances, overall, the discourses analyzed demonstrate the focus on the drug treatment as exclusive to dealing with the epidemic, leaving complex subjectivities that affect human beings diminished by the biomedical discourse, when biopolitics comes into play. Therefore, the discourse analyzed in the campaign did not contribute robustly enough to transform the stigma that triggers prejudice and discrimination.